My reckless surrender - Campbell, Anna (Avon romance., 2010)
Diana Croft has very good reasons for seducing Tarquin Vale, Earl of Ashcroft but instead of the selfish, jaded debaucher she discovers a man who stirs her deepest desires. The Earl is intrigued but is convinced she is consealing a dangerous secret and only after confronting this secret can he claim the woman who is his destiny.